Complement Deposition Predicts Worsening Kidney Function and Underlines the Clinical Significance of the 2010 Renal Pathology Society Classification of Diabetic Nephropathy - Jiang, Shimin; Di, Dingxin; Jiao, Yuanyuan; Zou, Guming; Gao, Hongmei; Li, Wenge (Frontiers in Immunology, 2022)
Objectives Converging evidence points towards a role of the complement system in the pathogenesis of diabetic nephropathy (DN). The classification system of diabetic kidney lesions devised by the Renal Pathology Society (RPS) in 2010 are based on the pathogenic process of DN. Therefore, we investigated the correlation between glomerular C3 deposits and RPS DN classification and the combined deleterious effects thereof on kidney function. Methods The study analyzed data from 217 diabetic patients who underwent renal biopsy between 2010 and 2021 and were found to have DN as the only glomerular disease. C3 deposition was considered positive if the glomerular C3 immunofluorescence intensity was at the trace or ≥1+ level. We divided DN into five glomerular lesion classes and separately evaluated the degree of interstitial and vascular involvement. The primary outcome was the composite of a ≥50% decline from the initial estimated glomerular filtration rate, end-stage renal disease, and death. Results None of the patients were classified into class I, and few were classified into classes IIa (7.8%) and IV (9.2%). Most patients were classified as IIb (30.9%) and III (52.1%). C3 deposition was detected in 53.9% of patients. Multivariate logistic regression analysis showed that DN class was significantly correlated with C3 deposits [odds ratio, 1.59; 95% confidence interval (CI), 1.08–2.36; p = 0.02). During a median follow-up of 22 months, 123 (56.7%) patients reached the composite outcome. The endpoints occurred more frequently in patients with C3 deposition (69.2 vs. 42%) compared with those without C3 deposition. Patients with C3 deposition in either class IIb [hazards ratio (HR), 3.9 (95% CI, 1.14–13.17) vs. 2.46 (95% CI, 0.68–8.89)] or III [HR, 4.98 (95% CI, 1.53–16.23) vs. 2.63 (95% CI, 0.77–9.0)] had a higher risk of adverse kidney outcomes than those without C3 deposition. The prognostic accuracy of the combination of DN class and C3 deposits at 1 and 3 years was higher than that for DN class only. Conclusions Complement deposition together with DN class predicts more rapid deterioration of kidney function in DN, which underlines the clinical significance of the DN phenotype according to the RPS classification.